International migration, land use change and the environment in Ixcán, Guatemala. (July 2016) - Taylor, Matthew J.; Aguilar-Støen, Mariel; Castellanos, Edwin; Moran-Taylor, Michelle J.; Gerkin, Kody
Highlights: This study shows that remittances sent back by migrants in the USA to Guatemala change land use patterns. We used a mixed methods approach to investigate in detail land use changes. Migrant households are in a better position to acquire land. Larger commodity production trends, particularly African Palm have a direct effect on land use, also in migrant households plots. Abstract: International migration flows between Guatemala and North America are now over thirty years old. The maturation of this phenomenon permits us to look beyond the immediate impacts of migrants and their remittances on Guatemalan livelihoods and to view how migration processes affect Guatemala's most valuable natural resource – land. We combine an interdisciplinary approach and data from a longitudinal study (1986–2012) that includes qualitative and quantitative methods to uncover and understand the specific impacts of international migration on land use and land distribution in San Lucas, Ixcán. We show that initial migration-related changes to land are not unidirectional and permanent. For example, after initial forest decline related to investment of cash remittances in cattle and pasture, the community experienced some forest recovery. This recovery can be explained by three processes. First, migrant money allowed some families to break their ties and reliance on the land and engage in non-agricultural occupations. Second, cleared land also reverted to forest because some migrant families failed in the technical and expensive business of raising cattle. Third, some farmers took advantage of national forestry incentives and left all or part of their parcels forested. However, as San Lucas and Ixcán become more integrated into the national economy, other options are open to migrant families. For example, in the last five years, some land owners took advantage of nearby expansion of the biofuel economy and improvement in roads and converted their fields to cultivate African Palm.